2021
DOI: 10.1016/j.jcot.2020.10.032
|View full text |Cite|
|
Sign up to set email alerts
|

Intra-operative referencing technique is non-inferior to use of fluoroscopy for acetabular component positioning in anterior hip arthroplasty

Abstract: Background: Intra-operative fluoroscopy has been shown to improve the accuracy of acetabular component positioning when compared to no fluoroscopy in direct anterior approach (DAA) total hip arthroplasty (THA). Due to logistical reasons, our senior author has been performing DAA THA at one institution without the use of fluoroscopy and has created an intraoperative referencing technique to aid in acetabular component positioning. The purpose of this study is to evaluate the accuracy of acetabular component pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…To date, it remains unclear whether the benefit of intraoperative fluoroscopic control of the component position outweighs the potential disadvantages related to its use (longer operation times, higher costs and radiation exposure) [6,7]. Individual studies either failed to show a significant difference or found only small differences [8][9][10][11][12][13][14][15][16][17]. A formal meta-analysis on this topic has not been published.…”
Section: Introductionmentioning
confidence: 99%
“…To date, it remains unclear whether the benefit of intraoperative fluoroscopic control of the component position outweighs the potential disadvantages related to its use (longer operation times, higher costs and radiation exposure) [6,7]. Individual studies either failed to show a significant difference or found only small differences [8][9][10][11][12][13][14][15][16][17]. A formal meta-analysis on this topic has not been published.…”
Section: Introductionmentioning
confidence: 99%